2019
DOI: 10.18203/2394-6040.ijcmph20193987
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening opportunistic screening for hypertension: report from a tertiary care institution in a district of West Bengal, India

Abstract: Background: Hypertension is a major public health problem in India and considered as a silent killer disease. The national program for prevention and control of cancer, diabetes, CVD and stroke (NPCDCS) recommended opportunistic screening for hypertension at all levels health facility. The present study was conducted with the objectives to estimate the magnitude of hypertension among the General OPD attendees aged 18 years and above in tertiary care hospital in a district of West Bengal and to find out the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other study reported the prevalence of hypertension to be 17%, 17.9%, 21.5%, while another study reported it to be 41.3%. 5,[9][10][11] Hypertension is a risk factor for cardiovascular diseases. The presence of this health condition may go unnoticed for long years, while opportunistic screening is simple, yet efficient method for screening hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other study reported the prevalence of hypertension to be 17%, 17.9%, 21.5%, while another study reported it to be 41.3%. 5,[9][10][11] Hypertension is a risk factor for cardiovascular diseases. The presence of this health condition may go unnoticed for long years, while opportunistic screening is simple, yet efficient method for screening hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Part 1: Socio-demographic profile and different factors associated with hypertension and obesity were included in the questionnaire, based on literature review. 5,9 Part 2: Measurement of BP, Height, Weight, BMI, Waist circumference.…”
Section: Data Collection Toolmentioning
confidence: 99%